The risk of cataract in relation to metal arc welding - Slagor, Rebekka Michaelsen; La Cour, Morten; Bonde, Jens Peter (Scandinavian Journal of Work, Environment & Health, 2016)
' ' OBJECTIVES ': 'There are indications that solar ultraviolet radiation (UVR) increases the risk of cataract, but there is only circumstantial evidence that metal welding, an important occupational source of UVR exposure, is a risk factor. The objective of this study is to unravel if metal welding increases the risk of cataract. ' ' METHOD ': 'We compared the risk of being diagnosed with cataract from 1987–2012 in a historic cohort of 4288 male metal arc welders against a reference group comprised of Danish skilled and unskilled male workers with similar age distribution. For the welders’ cohort, information on welding was collected from questionnaires and, for both cohorts, information about cataract diagnosis and operation was gathered from Danish national registers. Using Cox regression analysis, the hazard ratio (HR) for cataract diagnosis and/or operation was calculated in the follow-up period adjusted for baseline data regarding age, diabetes, and social group. ' ' RESULTS ': 'There were 266 welders and 29 007 referents with a diagnosis and/or operation for cataract. The unadjusted HR for cataract comparing ever-welders with referents was 1.07 [95% confidence interval (95% CI) 0.95–1.21] and the adjusted HR was 1.08 (95% CI 0.95–1.22). Age and diabetes were as expected strong risk factors. ' ' CONCLUSION ': 'We found no increased risk of developing cataract among Danish metal welders who worked with arc welding from 1950–1985. This may be attributed to the effectiveness of personal safety equipment.
Keywords: cataract; eye disease; metal arc welding; occupational; ultraviolet radiation; welder; welding